Impact of Climate Change on Aquatic Food Resources and Human Health in Iwofe, Port Harcourt - Amuda-Kannike, Abiodun; Amuda-Kannike, Abdulkareem; Chika, Chibuzor (Faculty of Natural and Applied Sciences Journal of Basic and Environmental Research, 2025)
This study investigates the impact of climate change on aquatic food resources and human health in Iwofe, Port Harcourt. Iwofe is a riverside community. It depends heavily on fish and other aquatic foods. These are the main sources of protein and income for the people. The problem is that climate change is causing serious issues. These include rising water temperatures, sea-level rise, and increased flooding. These changes affect the availability and safety of aquatic foods. This study used a descriptive survey research design. A sample of 180 residents and 50 fishers were selected through random sampling. Data was collected using a structured questionnaire and interviews. The data was analyzed using mean scores and chi-square tests. Findings showed that climate change has reduced fish catches significantly. It has also led to contamination of water bodies. This contamination causes health problems like cholera and diarrhea. The study concludes that climate change poses a major threat to food security and public health in Iwofe. It recommends community education on sustainable practices. It also calls for government action to build resilience and improve sanitation.